Implementasi Kebijakan Pelayanan pada Pasien Puskesmas Balaraja di Kabupaten Tangerang - Noviani, Emi; Supriady Bratakusumah, Deddy; Puspita Dewi, Maya (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This study was conducted to analyze the implementation of patient service policies at the Balaraja Health Center, Tangerang Regency. This study uses a descriptive and qualitative approach. Researchers collected data by observing and interviewing informants to capture the whole phenomenon in the field so that an overview of the implementation of service policies on patients at the Balaraja Health Center was obtained. The data analysis technique used is data source triangulation. Data analysis is carried out before entering the field, during the field, and after completion in the field. Data validity starts with reduction, data presentation, and concluding. Assessment of service quality in Balaraja Health Center patients uses an analysis of 5 Service Quality (ServQual) dimensions: Reliability, Empathy, Responsiveness, Assurance, and Tangible. The results showed several things complained about by informants, which were relatively entirely a lot in the dimensions of reliability, empathy, assurance, and tangible. The things complained about by informants in each dimension need to be a concern of the leadership and staff of the Balaraja Health Center, the Head of the Tangerang District Health Office, and the Tangerang Regent because it will affect patient satisfaction with the services provided by the Balaraja Health Center. In particular, improving the quality of services such as friendly service and not lingering, the layout of goods, and providing a budget for repairing existing damage. In the future, developing a program to expand the building and parking lot is necessary.